Factors Associated with Increasing Incidence of Burns among Adult Patients Admitted in the Kenyatta National Hospital Burns Unit - Amakobe, Nelly Cherop (Journal of Health, Medicine and Nursing, 2017)
Purpose: The purpose of this study was to establish the factors associated with increasing incidence of burns among adult patients admitted in the Kenyatta National Hospital burns unit. Materials and methods: The population of this research consisted of all patients in the burns unit at Kenyatta hospital. The study used primary data in particular used questionnaires. The questionnaire consisted of structured closed ended statements. Data was analyzed using Statistical Package for Social Sciences (SPSS) mainly by use of descriptive statistics. Descriptive statistics included mode, mean, median, standard deviation. Data was presented by use of graphs, pie charts and tables. Results: The study findings indicated that there has been an increase in number of patients with burns which is associated with various factors such as demographics factors, knowledge related factors and social economic factors causing the increased incidences among the patients. Specifically, poverty, overcrowding, having more than 3 children in the house, illegal electricity connection, lack of access roads and solid waste accumulation were identified as significant risk factors associated with injury in general. It can be concluded that demographics factors also led to increased incidences of burns due to low education and occupation hence forcing people to live in challenging areas. Recommendations: From the study findings the researcher recommend that it's important to educate the citizens in order to make them more aware of the dangers associated with various factors such as illegal electricity connection and lack of access roads. In doing this more cases of fire would be reduced and reduce loss of lives and property in more fire prone areas. The study also recommends that the Government through the Ministry of Public Health and Sanitation should impart knowledge related to the burns especially on how people can take preventive measures and emergency measures against fire outbreak.